Analysis and Evaluation of the Interrelation ships of the Labor Market Indicators of the Regions (Marzes) of the RA and the City of Yerevan - Tadevosyan, Zoya; Davtyan, Kamo; Matevosyan, Diana («Տնտեսագետ» հրատ․)
Issues in the field of employment basically predetermine both the current trends in the economic development of any country and long-term expectations. Therefore, the analysis of employment indicators and their qualitative and quantitative assessment form sufficient practical grounds for an objective and scientific solution to the problems of economic activity of the population. In this article, the indicators characterizing the employment market of the territorial units of the Republic of Armenia, including the city of Yerevan, were analyzed, using econometric models. And the relationship and interaction between macroeconomic indicators and employment indicators were evaluated. The results of the analysis show that, according to territorial units, both employment indicators and other macroeconomic indicators in Armenia are highly polarized, and positive trends in economic development are manifested mainly in Yerevan and Syunik regions. The results of econometric models "economic growth - reduction of unemployment", in turn, reveal the gap between the capital and the regions in terms of reducing unemployment.
Keywords: Social policy